Digital Transformation: Overcoming History Learning Boredom through Interactivity at SMA Negeri 1 Giri - Ester Carolina Putri Nugraha; Ainul Yaqin; Putri Nadiah; Intan Melani Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Conventional history learning at SMA Negeri 1 Giri, Banyuwangi, often triggers boredom among 11th-grade student due to the dominance of lecture and memorization methods, as evidenced by initial observations depicting lethargic students and complaints of monotony. This wualitative case study researcch integrates findings from student observation reports at Universitas 17 Agustus 1945 banyuwangi (Oktober 2025) and supplementary materials on academic boredom and digital interactivity, exploring tranformation trough gamification (Kahoot), multimedia (local Banyuwangi videos), and collaborative platforms (padlet) to address four research questions. Data from participant observations, in-depth interview (20 studens, 5 teachers), and document analysis of teaching modules across two PTK cycles (December 2025-January 2026) reveal a student narrative shift from “class like a graveyard” to “history like an exciting game.” Supporting factors include the flexible ATP of the merdeka Curriculum and teacher enthusiasm, while barriers like weak signals were overcome via hybrid mode. The findings enrich rural education practices, affirming that digital interactivity brings relevant history to life in the with the pancasila student profile.